2014
DOI: 10.7863/ultra.33.12.2087
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic Assessment of Healthy Peripheral Joints

Abstract: Sonographic changes in healthy peripheral joints were observed predominantly in the oldest group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…MSUS is an easily accessible diagnostic tool and a therapeutic option in patients with inflammatory arthritis including rheumatoid arthritis (RA) and OA [14,15]. Although most articular fluid is distributed throughout the joint recesses, the joint spaces between the articular surfaces are relatively small in healthy people [3]. High-resolution ultrasonography allows one to assess fine details in anatomical structures [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MSUS is an easily accessible diagnostic tool and a therapeutic option in patients with inflammatory arthritis including rheumatoid arthritis (RA) and OA [14,15]. Although most articular fluid is distributed throughout the joint recesses, the joint spaces between the articular surfaces are relatively small in healthy people [3]. High-resolution ultrasonography allows one to assess fine details in anatomical structures [5].…”
Section: Discussionmentioning
confidence: 99%
“…Reliable application of MSUS requires knowledge of the normal articular anatomy and its variation. Assessment of cartilage thickness is important when distinguishing between normal and pathological conditions, evaluating the severity, monitoring disease progression during long-term follow-up, and assessing the efficacy of disease-modifying OA drugs [3]. As the numbers of clinical trials employing MSUS increase, appropriate assessment of articular cartilage morphology and periarticular status is becoming more important.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of synovial abnormalities in our study was comparable with these previous studies, suggesting similar findings in diverse populations (China, USA, UK, and Italy). Several previous studies also reported higher prevalence of synovial hypertrophy and effusion in men than women [ 20 , 21 , 33 ]. This finding may be partly explained by the fact that men normally have thicker synovium and more synovial fluid than women [ 21 ].…”
Section: Discussionmentioning
confidence: 70%